-3a-8(-5a-1)=

Simple and best practice solution for -3a-8(-5a-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3a-8(-5a-1)= equation:


Simplifying
-3a + -8(-5a + -1) = 0

Reorder the terms:
-3a + -8(-1 + -5a) = 0
-3a + (-1 * -8 + -5a * -8) = 0
-3a + (8 + 40a) = 0

Reorder the terms:
8 + -3a + 40a = 0

Combine like terms: -3a + 40a = 37a
8 + 37a = 0

Solving
8 + 37a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 37a = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 37a = 0 + -8
37a = 0 + -8

Combine like terms: 0 + -8 = -8
37a = -8

Divide each side by '37'.
a = -0.2162162162

Simplifying
a = -0.2162162162

See similar equations:

| 4p^2+164p+81=0 | | (3x-9)=(2x+31) | | B-4+6b=23 | | 1/6-3x/2=x/4-1/4 | | 3x-4(x+2)=3(4-2x)+8 | | 3/2=21/x | | 3x-1/2x | | b+.66666=2 | | f(1/2)=1/2+9.5 | | -17+20= | | -6(v-4)=18-5v | | x/6-x/12+8=x+8 | | 5y-8-3y+3=0 | | 3/4w=75 | | V-24=-7 | | 12y^2-22y+6=0 | | 8x-2=20x+7 | | 3z-2+5=9 | | x^2=(6/11x)+(135/121) | | -9-(-11)= | | (2x+3)(x)=37 | | 2x+8/4=7x-10/9 | | x(7+x)=6(4+6) | | 2-1/x-5/x^2=0 | | 28+3=x | | -2a4/-3b-7 | | 1/7-2/7j=3/14 | | 38=5x-4+8x-10 | | f(-3)=-3+9.5 | | 12r^2-36r-144=0 | | .33x-1.33=.75x-1.6 | | r^2-6r+10=0 |

Equations solver categories